“The Graying Minority”: Lived Experiences and Psychosocial Challenges of Older Transgender Adults During the COVID-19 Pandemic in India, A Qualitative Exploration - Banerjee, Debanjan; Rao, T. S. Sathyanarayana (Frontiers in Psychiatry, 2021)
Background: The Coronavirus disease 2019 (COVID-19) has emerged as a global health threat. Certain factors like age, an immunocompromised state, and social impoverishment, etc. can add to health vulnerabilities during this pandemic. One such group is older transgender adults, who often bear a combination of these risks. As the world is aging fast, their numbers have also been increasing. With this in mind, this study explores the lived experiences and psychosocial challenges of older transgender adults during the COVID-19 pandemic in India. Methods: A qualitative approach was used. Ten individuals with “transgender” identity above the age of 60 were recruited with consent through purposive sampling. In-depth interviews were conducted on the telephone using a pre-designed interview schedule. They were recorded, translated, and transcribed verbatim. Hasse's adaptation of Colaizzi's phenomenological method was used for analysis. Independent coding and respondent validation were used to ensure the rigor of data. Results: The super-arching categories (with themes) were marginalization (“second” priority, stigma, social disconnection), the dual burden of “age” and “gender” (ageism, othering, and psychosexual difficulties), and multi-faceted survival threats (physical, emotional, financial) during the pandemic. Social rituals, spirituality, hope, and acceptance of “gender dissonance” emerged as the main coping factors, whereas their unmet needs were social inclusion, awareness related to COVID-19, mental health care, and audience to their distress. Conclusion: The elderly gender minorities are at increased emotional and social risks during the ongoing pandemic, and their voices are mostly unheard. The need for policy implementation and community awareness about their social welfare is vital to improving their health and well-being.